2017
DOI: 10.5005/jp-journals-10019-1167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Correlation between the Vertical Dimension of Occlusion and the Length of the Ear, Nose, and Little Finger: An Anthropometric Study

Abstract: Introduction:The aim of this study was to find out the anthropometric correlation of vertical dimension of occlusion (VDO) with the length of ear, nose, and little finger in dentate male and female subjects in Karad population, so as to use this correlation to determine VDO in edentulous patients. Materials and methods:The study was conducted in Krishna Institute of Medical Sciences Deemed University, Karad, India, on 320 dentate subjects (160 males and 160 females) who fulfilled the inclusion criteria. Anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Similar study was conducted by Nagpal et al, where they found a non significant relationship of this dimension with vertical dimension at occlusion. 14 In another study, conducted by Rege et al evaluated a significant correlation of length of nose with that of VDO in case of females, 15 supporting our study where statistically significant results were seen in cases of females (0.000) and a significant result in case of males.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar study was conducted by Nagpal et al, where they found a non significant relationship of this dimension with vertical dimension at occlusion. 14 In another study, conducted by Rege et al evaluated a significant correlation of length of nose with that of VDO in case of females, 15 supporting our study where statistically significant results were seen in cases of females (0.000) and a significant result in case of males.…”
Section: Discussionsupporting
confidence: 86%
“…As such there are no or minimal studies which correlated the length of ear with that of vertical dimension at occlusion. One of the studies, conducted by Rege et al 15 in 2017 and Prajapati et al 16 in 2015 evaluated the correlation of vertical dimension of occlusion and length of ear. A statistically significant correlation was observed in case of length of ear in males with a value of 0.500 in their study, which was in consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Eye-Mouth distance, the study results were consistent with Mcgee, 8 Alhajj et al, 9 Bajunaid et al, 14 and Nagpal et al, 19 Though an agreement with Chou et al, 21 Abdul-Rassol et al, 15 Nagpal et al, 19 and Alhajj 22 considering the validity of Eye-Ear distance was noticed, a variance with Miran et al, 12 and Bajunaid et al14 results was reported. In view of vertical ear height, the coefficients of correlation in Prajapati et al, 23 and Rege et al, 24 studies were (r= 0.640) and (r=0.500), respectively, which import superior figures to these study observations (r= 0.290). On the other hand, Bajunaid et al, 14 reported a weak correlation for this parameter.…”
Section: Resultsmentioning
confidence: 50%
“…Many methods have been documented in literature for registering the accurate vertical dimension but none has universal acceptability 11,12 . The reason could be explained on the basis of the variation existing in the physiological characteristics of the individual across the world [10][11][12] Various methods including preextraction records, phonetic method, cephalometery and facial measurements have been used as useful tools in recording accurate vertical dimension.None of the above methods is accurate and every method has its limitations 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Pre -extraction records are said to be inexpensive, stable and reusable records 9,11,12 . Few old studies have taken preextraction measurements from anterior region to determine occlusal vertical dimension 13 .…”
Section: Introductionmentioning
confidence: 99%